Peningkatan Profesionalitas Guru SDN Sumurwelut III Melalui Pelatihan Publikasi Karya Ilmiah - Via Yustitia; Danang Prastyo; Bahauddin Azmy; Dian Kusmaharti; Bramianto Setiawan; Alfredo Ibara Febriant Utomo; Wima Hayu Wasesa (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Publication of scientific papers is one of the demands of a continuous professional development model for teachers. The obligation of scientific publications enhances the tradition of a teacher's scientific culture. This is also related to the increase in the teacher's functional position and the credit score. But in reality, scientific publications for teachers are still in the sufficient category. The partner for this community service activity is SDN Sumerwelut III, where the problem faced is the teacher's lack of knowledge in technical terms of publishing scientific papers. In addition, it is a new thing for SDN Sumerwelut III to publish in OJS-based scientific journals. This PKM activity provides a solution for partners in the form of OJS-based scientific work publication training so that teacher professionalism increases. The objectives of this activity: (1) Provide teachers with an understanding of the urgency of scientific research and publication as part of the teacher's professionalism obligations in developing knowledge; (2) Provide additional knowledge about the publication of scientific papers; (3) Introducing OJS-based online scientific journals as a forum for teachers to publish scientific papers. Activities are carried out through intensive training and mentoring methods.